Student's learning style and lecturer's teaching style. Do the two meets? / Marni Ghazali - Ghazali, Marni; Arifin, Suliana (2005)
Teaching and learning styles, either match or mismatch has become the main issue in higher education system. The match between teaching and learning will offer a good implication to the education system.